Towards Detection of Glycoproteins Using Molecularly Imprinted Nanoparticles and Boronic Acid-Modified Fluorescent Probe - Lingdong Jiang (Polymers, 2019)
Glycoproteins represent a group of important biomarkers for cancer and other life-threatening diseases. Selective detection of specific glycoproteins is an important step for early diagnosis. Traditional glycoprotein assays are mostly based on lectins, antibodies, and enzymes, biochemical reagents that are costly and require special cold chain storage and distribution. To address the shortcomings of the existing glycoprotein assays, we propose a new approach using protein-imprinted nanoparticles to replace the traditional lectins and antibodies. Protein-imprinted binding sites were created on the surface of silica nanoparticles by copolymerization of dopamine and aminophenylboronic acid. The imprinted nanoparticles were systematically characterized by dynamic light scattering, scanning and transmission electron microscopy, thermogravimetric analysis, Fourier transform infrared spectroscopy, and elemental analysis. A boronic acid-modified fluorescent probe was used to detect the target glycoprotein captured by the imprinted nanoparticles. Using horseradish peroxidase as a model glycoprotein, we demonstrated that the proposed method can be applied to detect target protein containing multiple glycosylation sites. Because of their outstanding stability and low cost, imprinted nanoparticles and synthetic probes are attractive replacements of traditional biochemical reagents to develop simpler, faster, and more cost-effective analytical methods for glycoproteins.